Ultrafast Growth of h-MoO3 Microrods and Its Acetone Sensing Performance - Santos, Giovana T. [UNESP]; Felix, Anderson A. [UNESP]; Orlandi, Marcelo O. [UNESP] (Mdpi, 2021)
Hexagonal molybdenum trioxide (h-MoO3) was synthesized by microwave-assisted hydrothermal method, allowing an ultrafast growth of unidimensional microrods with well-faceted morphology. The crystalline structure of this metastable phase was confirmed by X-ray diffraction (XRD) and Raman spectroscopy. Scanning electron microscopy (SEM) showed that hexagonal microrods can be obtained in one minute with well-defined exposed facets and the fine control of morphology. Sensing tests of the acetone biomarker revealed that the h-MoO3 microrods exhibit, at low ppm level, good sensor signal, fast response/recovery times, selectivity to different interferent gases, and a lower detection limit of 400 ppb.
Keywords: h-MoO3; hydrothermal; microwave; acetone; gas sensing